ドンファン コボン ノ エンルイ ノ カガク セイブン ノ キゲン ニ ツイテ - 冨山, 千里; トヤマ, チサト; 北野, 康; キタノ, ヤスシ; 鳥居, 鉄也; トリイ, テツヤ; Tomiyama, Chisato; Kitano, Yasushi; Torii, Tetsuya (1983)
P(論文) 南極, ドライバレーのドンファン湖盆から採取した, 柱状コア7本について, そこに含まれている水溶性の塩類を分析し, 主成分と少量成分の含有量の比から, 過去の湖水の組成を推察した。また, 水不溶性の部分については, 分別溶解法を用いて分析をおこない, 各構成鉱物への, Ca, Mg, Fe, Mnの分配を明らかにした。それらの分析値を用いて, 現在のドンファン湖盆に存在する塩類の総量を見積もった。その結果, ドンファン湖盆の塩類の起源である塩水は, Mgが非常に少ないCaCl_2型の水ではないかと考えられる。 Water soluble salts in seven sediment cores, which were taken from the Don Juan basin in the Dry Valleys region, Antarctica, were analyzed. The chemical composition of the original pond water was presumed from the contents of minor components as well as major components in the water soluble salts. The partitioning of Ca, Mg, Fe and Mn into each mineral in the water insoluble portion of the sediment was clarified by using a selective chemical leaching technique. The total amounts of salts in the Don Juan basin were estimated from these analytical data. As a result, the original brine for the salt in the Don Juan basin was supposed to be a calcium chloride type water with a low magnesium content. departmental bulletin paper